Cash social assistance Covid-19, welfare, and economic performance in Indonesia - Hermawan, Iwan; Widyarini, Maria (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2023)
The Cash Social Assistance Covid-19 (BST Covid-19) aims to help the community affected by the Covid-19 pandemic. However, the assistance index (the social assistance amount per household), which is relatively small and has a uniform magnitude, is